Import Competition and U.S. Sentiment Toward China - Rabah Arezki; Duong Trung Le; Ha Nguyen; Hieu Nguyen (Center for Economic Studies and ifo Institute (CESifo), 2024)
We empirically examine how import competition affects sentiment toward China in local communities in the United States using a news-based index for sentiment. Results are threefold. First, U.S. sentiment toward China peaked in 2007 before turning negative. Second, communities more exposed to import competition from China have experienced a greater deterioration in sentiment. Third, the trade-induced U.S. sentiment toward China is broad-based, encompassing political, military, and national security issues. These findings suggest that competition over trade may have important geopolitical implications through sentiment of local communities.
Keywords: E24; F14; F16; J23; J31; L60; O47; R12; R23; 330; import competition; sentiment; fragmentation